Complex-Structure Resource Management in Engineering and Construction - Roman Marcinkowski (Communications - Scientific letters of the University of Zilina, 2002)
The original issue solved in this article is the model of analyzing hierarchical-structure resources ensuring controlling the availability and engagement of the resources in allocating units of a complex structure for given works. This model is applicable when designing the decision facilitation systems in planning military and engineer operations. “Qualifying” the units of such structures using the computer requires taking under consideration the fact of units “nesting” in others. Apart from the method of “qualifying” complex resources, in this work has been formulated a model of allocating a hierarchical structure for works on the separated work fronts. The model enables an automation of calculations aimed at designating the contractor for the set of tasks executed on work fronts, based on their labor consumption referred to the resources of any of the levels of a hierarchical structure.